Commentary on "Effects of upper limb vibratory stimulation training on motor symptoms in Parkinson's disease: an observational study" - Mebanpynjop Dohtdong; Shanika Sharma; Varun Kalia (Medical Journals Sweden, 2024)
Abstract missing (Commentary)